2001
DOI: 10.1111/j.1432-2277.2001.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 expression as a possible predictive parameter for subclinical renal allograft rejection

Abstract: In the present study we have tried to establish the role of IL-17 in subclinical renal allograft rejection. In this animal model, renal grafts from BN (RT1n) were transplanted heterotopically into LEW (RT1l) rats. As controls, LEW grafts were transplanted into LEW rats. The histopathological examination demonstrated that the changes in the allograft kidney on day 2 were similar to those ranked as borderline changes according to the Banff classification scale. On day 2, the serum level of blood urea nitrogen (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…Elevated IL-17 levels have been associated with renal and lung graft rejection in humans (Loong et al, 2002;Vanaudenaerde et al, 2008). Study in acute rat renal allograft rejection model has also identified an elevation of IL-17 protein as early as 2 d after transplantation (Hsieh et al, 2001). Th17 expression was markedly increased in inflamed transplants and draining lymph nodes at the early stage of allocorneal rejection in mouse (Chen H. et al, 2009).…”
Section: Cd4mentioning
confidence: 91%
“…Elevated IL-17 levels have been associated with renal and lung graft rejection in humans (Loong et al, 2002;Vanaudenaerde et al, 2008). Study in acute rat renal allograft rejection model has also identified an elevation of IL-17 protein as early as 2 d after transplantation (Hsieh et al, 2001). Th17 expression was markedly increased in inflamed transplants and draining lymph nodes at the early stage of allocorneal rejection in mouse (Chen H. et al, 2009).…”
Section: Cd4mentioning
confidence: 91%
“…As their clinical significance in autoimmune disorder has been revealed, the interplay between Treg and Th17 cells is now of interest in transplantation (Loong et al, 2000;Hsieh et al, 2001;San Segundo et al, 2008;Crispim et al, 2009;Mitchell et al, 2009). However, the significance of their interplay has not been investigated in acute T cell-mediated rejection (ATCMR).…”
Section: Foxp3mentioning
confidence: 99%
“…Moreover, elevated IL-17 mRNA and protein levels could be detected in renal biopsy specimens and urinary sediment from patients found to have subclinical rejection when compared with control samples without any evidence of rejections (Loong et al 2002). Additionally, elevated IL-17 mRNA and protein levels were detectable as early as the second post-operative day in a rat renal allograft model and its appearance is followed by the local production of pro-inflammatory molecules known to be induced by IL-17 (Hsieh et al 2001).…”
Section: Il-17 In Transplantationmentioning
confidence: 79%